The role of vagal nerve stimulation on psychosocial associated disorders in refractory epilepsy patients - Mohamed Abdul Jalil Al-Tamimi (Journal of the Pakistan Medical Association, 2024)
Objectives: To determine the effects of vagal nerve stimulation on cognition and epilepsy-associated psychosocial problems in patients with intractable epilepsy, and to assess their relation to seizure decline. Method: The longitudinal study was conducted at Saad Al-Witry Neurosciences Hospital, Baghdad, Iraq, from December 2015 to December 2020, and comprised refractory epilepsy cases with implanted vagal nerve stimulation devices. They were subjected to pre- and post-implantation epilepsy protocol assessment with added neuropsychological evaluation using the Mini-Mental State Examination system. Each case was followed up for 2 years post-implantation. Descriptive data regarding patient records of age, seizure nature, mental functioning level, and vagal nerve stimulation insertion was noted. Data was analysed using SPSS 21. Results: Of the 150 patients, 75(50%) each were males and females, with 70(46.7%) aged <10 years at the time of surgery. Overall, 80(53.3%) patients had partial seizures with secondary generalisation, 70(46.7%) had refractory seizure attacks for <5 years, 78(52%) had attack frequency of 2-5 per day. All 150(100%) patients had had vagal nerve stimulation for >2 years. Post-intervention, 80(53.3%) patients had <2 attacks per day. Mini-Mental State Examination score was >25 in 35(23.3%) patients which post-intervention rose to 64(42.7%). Conclusion: There was evidence of improvement with respect to patient characteristics predictive of vagal nerve stimulation-related cognition and neuropsychological responsiveness in refractory epilepsy. Key Words: Vagus Nerve, Cognition, Seizures